Measurements of Radon-222 and its Daughters Concentrations in Buildings of Department Physics in College of Sciences of Baghdad University - Baghdad Science Journal (مجلة بغداد للعلوم)
The present work aims to investigate approaches, measures and detection of indoor radon level in buildings of the department of physics in college of science of Baghdad University. CR-39 solid state nuclear track detectors were used to measure the radon concentrations inside the rooms, including five laboratories and five workplace rooms in ground and first storey of the department. The average radon concentration at first storey was found to be 43.1±13.2 Bq/m3 and 40.1±13.4 Bq/m3 at the ground storey. The highest level of radon concentration at the first storey in the radioactive sources store was 87.5±29 Bq/m3 while at the ground storey in room(2) was 70.2±24 Bq/m3 which is due to the existence radioactive sources in some selected places at the buildings.